Evaluation Of Some Insecticides Against Tomato Leaf Minor (Tuta Absoluta) And Determination Of Their Residues In Tomato Fruits (Applied Biological Research, 2012)
Recently tomato leaf miner, Tuta absoluta, has become one of the most  devastating pests of tomato in Egypt, and caused serious damages to  tomato production in invaded areas. For this reason, the present study  was undertaken to determine the efficacy of 15 insecticides representing  different pesticide groups against this insect and also to study their  dissipation in tomato fruits. The laboratory experimental results revealed that profenofos, cyfluthrin, lufenuron, chlorpyriphos-methyl and  indoxacarb were the most toxic insecticides as compared to other  chemicals. These insecticides, 1 day after application, under field  conditions caused 84.1 to 73.5% reduction in infestation. With time the  bio-residual activity of these compounds gradually decreased with  increase in the number of infested fruits. The initial deposits of  profenofos, cyfluthrin, lufenuron and chlorpyriphos-methyl ranged from  28.6 to 6.3 ppm, depending on the rate of insecticide application. The loss  rate of these amounted to 91.7 to 97.57%, 15 days after treatment. In  conclusion, all tested insecticides proved effective against T. absoluta and  might be used to control this pest. Further, the bioresidual activity of  these compounds did not exceed more than two weeks for the best cases.
Keywords: Insecticide efficacy; leaf miner; residues; tomato; Tuta absoluta